ISOLATION AND CHARACTERIZATION OF ANTINEOPLASTIC ALKALOIDS FROM CATHARANTHUS ROSEUS L. DON. CULTIVATED IN EGYPT - Shams, K. A.; Nazif, N. M.; Abdel Azim, N. S.; Abdel Shafeek, K. A.; El-Missiry, M. L.; Ismail, S. I.; Seif El Nasr, M. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Vinblastine and vincristine (the antileukemic agents) were isolated, in a pure form, from Catharanthus roseus L. Don., cultivated in Egypt, by several chromatographic techniques. Five modified methods for the preparation of total alkaloids were carried out. All the isolated mixtures were evaluated by HPLC and HPTLC analyses. The antineoplastic alkaloids; vinblastine and vincristine, were isolated by the use of vacuum liquid chromatographic column on silica gel : aluminium oxide (1:1) mixed bed vacuum liquid chromatography (VLC), Charcoal column, and finally purified by centrifugally accelerated radial chromatography (Chromatotrone).